Memori Kerja dan Kesalahan Penggunaan Partikel Kakujoshi oleh Calon Guru Bahasa Jepang - Febriyanti, Rike; Husna, Lailatul (Vocational College of Diponegoro University, 2024)
Particles in Japanese have a vital position and are very difficult for Indonesian Japanese learners. Inaddition to appearing very often, they also mark verbal arguments, mark additions and have semanticattributes, topical phrases and mark additional attributive nominals which when studied are recordedin the working memory of our brains. This study attempts to see the error in particle selection in theworking memory thinking framework carried out by students who will become prospective Japaneselanguage teachers. This study uses a qualitative and quantitative method of analysing the results ofrespondents' work. We can conclude that these prospective teachers have not received enoughsystematic time and opportunity to be able to place various Japanese language particles in theirworking memory so that they can use the right particles whenever they are faced with the opportunityto use the particles.